(untitled) (Bangladesh Journal of Botany, 2008)
Pollen grains of 20 taxa from two genera of the Liliaceae were examined and compared by LM (light microscope), SEM (scanning electron microscope) and pollens of four taxa were also examined with TEM (transmission electron microscope). Pollen grains shed as monads. They are monosulcate and ellipsoidal. Fritillaria crassifolia subsp. crassifolia Freyn & Smt. sometimes sheds the pollen as dyads. Exine is semitectate and the tectum is perforate. Columellae are simplicolumellate. Ectexine is thicker than endexine. Exine sculpture (ornamentation) is reticulate, reticulate-rugulate, rugulate and retipilate in Asparagus pollens and reticulate, suprareticulate, rugulate-reticulate and striate-reticulate in Fritillaria pollens. Sulcus extends from distal to proximal in some pollens of Asparagus and Fritillaria. Â Key words: Asparagus, Fritillaria, Liliaceae, Pollen morphology DOI = 10.3329/bjb.v36i2.1498 Bangladesh J. Bot. 36(2): 111-120, 2007 (December)